2006
DOI: 10.1111/j.1095-8339.2006.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic revision of the tribe Hymenodictyeae (Rubiaceae, Cinchonoideae)

Abstract: The palaeotropical tribe Hymenodictyeae Razafim. & B. Bremer, belonging to the otherwise predominantly Neotropical subfamily Cinchonoideae s.s. (coffee family or Rubiaceae), is revised here. The tribe as presently circumscribed contains two genera, Hymenodictyon Wall. and Paracorynanthe Capuron ex J.-F. Leroy, and is distinct from the other Cinchonoideae tribes with capsular fruits in having stipules bearing large, deciduous colleters on the margins, valvate corolla aestivation, and lenticellate capsular fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…(De Block, Degreef & Robbrecht, 2002), Gyrostipula J.‐F.Leroy (Emanuelsson & Razafimandimbison, 2007), Hymenodictyon Wall. with Paracorynanthe Capuron (Razafimandimbison & Bremer, 2006), Ixora L. (De Block, in press), Lathreaocarpa Bremek. (Groeninckx et al ., 2009b), Mantalania Capuron ex J.‐F.Leroy (De Block & Davis, 2006), Paederia L. (Puff, 1991), Paracephaelis Baill.…”
Section: Introductionmentioning
confidence: 99%
“…(De Block, Degreef & Robbrecht, 2002), Gyrostipula J.‐F.Leroy (Emanuelsson & Razafimandimbison, 2007), Hymenodictyon Wall. with Paracorynanthe Capuron (Razafimandimbison & Bremer, 2006), Ixora L. (De Block, in press), Lathreaocarpa Bremek. (Groeninckx et al ., 2009b), Mantalania Capuron ex J.‐F.Leroy (De Block & Davis, 2006), Paederia L. (Puff, 1991), Paracephaelis Baill.…”
Section: Introductionmentioning
confidence: 99%
“…10 The 1 H NMR spectrum of compound (1) ( [12][13][14][15] (gardenamide class), and some were obtained as metabolites produced by human 16 and rat intestinal bacteria. 17 Comparison with the published data of known iridoid alkaloids, such as (6) (Figure 1), and hemiacetal-secoiridoids 11,18 like (7) ( Figure 1) and compound (1) 11,18 showed that (1) it was neither a hemiacetal nor a nitrogen-containing iridoid (N-2) but that it was compatible with a C-1(N)O-2 substitution. This was also supported by the presence of the 1 H-1 H COSY correlation between H-1/NH, rather than the H-1/NH, H-3/NH correlations expected in the iridoid alkaloids, 17 and by UV and IR data indicating the presence of the chromophore -OOCC=CHO.…”
Section: Resultsmentioning
confidence: 98%
“…Of these, 11 are endemic to Madagascar, 4 to Asia and 7 to Tropical Africa. 1 Hymenodictyon floribundum B.L. Rob.…”
Section: Introductionmentioning
confidence: 99%
“…Within the tribe Hymenodictyoneae, Hymenodictyon is easily recognized by the thick, non-plated (i.e. more or less smooth) bark, and the ellipsoid, capsular fruit (Razafimandimbison & Bremer 2006).…”
Section: Introductionmentioning
confidence: 99%